A Comparative Clinical Study of Karanja Churna and Karanja Tail Yoni Pichu in the Management of Shwetapradar w.s.r. to Leucorrhoea. - nagar, Meenakshi; Jain, C M; Sharma, Sushila; Dave, Hetal H (International Research Journal of Ayurveda & Yoga, 2022)
Background And Aims- Shwetapradar (Leucorrhoea) is one of the most common of all gynecological complaints. In our text Shwetapradar is described directly or indirectly in many Yonirogas as a symptom. In the present study we have used two types of trial drugs namely Karanja Churna for oral route and Karanja Tail for local application as Yoni Pichu with the aim to validate the directives of classics on parameters of a systematic and scientific research work. Material And Method- The method adopted in present study is Randomized, clinical, open study. This study was done on randomly selected 45 patients which were divided in three groups of 15 patients in each group. All the patients results were assessed subjectively and objectively and statistical evaluation of results were done with ‘paired Wilcoxon signed rank test’ and ‘ unpaired ONE WAY ANOVA test’.Results- The results were assessed in the form of relief from the symptoms. The results showed that overall relief in group C patients were the highest which was (66.19%) followed by group B (61.38%) and group A (45.96%) Conclusion- This can be made out from the study that if both Karanja Churna & Karanja Tail Yoni Pichu are given simultaneously are more effective than Karanja Churna orally alone and Karanja Tail Yoni Pichu vaginally alone.